Colonic inflammation and secondary bile acids in alcoholic cirrhosis - Kakiyama, Genta (American Physiological Society, 2014)
Alcohol abuse with/without cirrhosis is associated with an impaired gut barrier and inflammation. Gut microbiota can transform primary bile acids (BA) to secondary BAs, which can adversely impact the gut barrier. The purpose of this study was to define the effect of active alcohol intake on fecal BA levels and ileal and colonic inflammation in cirrhosis. Five age-matched groups {two noncirrhotic (control and drinkers) and three cirrhotic [nondrinkers/nonalcoholics (NAlc), abstinent alcoholic for >3 mo (AbsAlc), currently drinking (CurrAlc)]} were included. Fecal and serum BA analysis, serum endotoxin, and stool microbiota using pyrosequencing were performed. A subgroup of controls, NAlc, and CurrAlc underwent ileal and sigmoid colonic biopsies on which mRNA expression of TNF-α, IL-1β, IL-6, and cyclooxygenase-2 (Cox-2) were performed. One hundred three patients (19 healthy, 6 noncirrhotic drinkers, 10 CurrAlc, 38 AbsAlc, and 30 NAlc, age 56 yr, median MELD: 10.5) were included. Five each of healthy, CurrAlc, and NAlc underwent ileal/colonic biopsies. Endotoxin, serum-conjugated DCA and stool total BAs, and secondary-to-primary BA ratios were highest in current drinkers. On biopsies, a significantly higher mRNA expression of TNF-α, IL-1β, IL-6, and Cox-2 in colon but not ileum was seen in CurrAlc compared with NAlc and controls. Active alcohol use in cirrhosis is associated with a significant increase in the secondary BA formation compared with abstinent alcoholic cirrhotics and nonalcoholic cirrhotics. This increase in secondary BAs is associated with a significant increase in expression of inflammatory cytokines in colonic mucosa but not ileal mucosa, which may contribute to alcohol-induced gut barrier injury.